Strategi Pengembangan Terhadap Optimalisasi Kinerja Karyawan (Studi Kasus: BMT Nuansa Ummat Cabang Pakong) - Sofiatun Imamah (Universitas Muhammadiyah Jember, 2021)
Resources are the ability to do things, and take advantage of existing opportunities, and the ability to be able to free yourself from the difficulties experienced. Every human being has une game-equal abilities, skills and creativity. BMT (Baitul Maal Wattamwil) is an institution that has two activities in an integrated manner. Baitul Maal is more directed to the efforts of collecting and disbursing funds that are nonprofit, such as: zakat, infaq, and alms. Baitul tamwil as an effort to collect and distribute commercial funds. The purpose of this research is to find out the development strategy in employee performance in human resource development strategy in optimizing employee performance in Baitul Maal Wa Tamwil (BMT) nuances of pakong pamekasan branch ummah. The type of research used is field. The nature of his research is descriptive cauldron. The research source uses primary data. The company's performance is an important thing that must be achieved by every company anywhere, because performance is a reflection of the company's ability to manage and allocate its resources